2003
DOI: 10.2190/7br8-vxa0-07a7-8avn
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Patterns of Searching the Web

Abstract: There has been a national call for increased use of computers and technology in schools. Currently, however, little is known about how students use and learn from these technologies. This study explores how eighth-grade students use the Web to search for, browse, and find information in response to a specific prompt (how mosquitoes find their prey). A previous analysis (Roy, Taylor & Chi, 2003) found that boys performed significantly better on gaining target-specific (information directly related to the prompt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 15 publications
8
52
1
Order By: Relevance
“…These findings were contradictory to the expectations based on earlier research (Large, Bahesti & Rahman, 2002;Roy & Chi, 2003). While both genders needed fewer revisits when given a tag cloud, males profited more from tag clouds than females.…”
Section: Navigating In Hypertext 23contrasting
confidence: 84%
See 1 more Smart Citation
“…These findings were contradictory to the expectations based on earlier research (Large, Bahesti & Rahman, 2002;Roy & Chi, 2003). While both genders needed fewer revisits when given a tag cloud, males profited more from tag clouds than females.…”
Section: Navigating In Hypertext 23contrasting
confidence: 84%
“…Research found that boys are more active in browsing than girls (Large, Bahesti & Rahman, 2002;Roy & Chi, 2003): they looked at more pages, selected more hyperlinks and saved more information, while they spent less time on viewing pages. It can be expected that learning outcomes are affected negatively as spending less time viewing pages might hamper comprehension.…”
Section: Individual Characteristics: Gender Differencesmentioning
confidence: 99%
“…Large, et al [47] on the other hand, found males to be generally more active in the way they searched the Web, clicking on more links per minute, and following up on more hits. Similarly, Roy and Chi [51] found that the overall pattern of search behaviour was different for males and females. Similarly, Vecchi and Girelli [26] explored gender differences in visuospatial tasks that either required memorizing (passive task) or manipulating and transforming (active task) visuospatial information.…”
Section: Discussionmentioning
confidence: 88%
“…However, the results for comprehension in the field are mixed, since some researchers have found that males performed better than females [34][35][36]. Roy and Chi [51] found that young males performed significantly higher than young females on both, target-specific and target-related information measures. Other researchers though have found that females were more successful in Web-based learning [33], and others have found no difference between genders [12,[17][18][19][20], similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they found that the male group was more actively engaged in browsing than the female group, and that the male group explored more hypertext links per minute. The other study by Roy and Chi (2003) examined gender differences in searching the web for information by analyzing students' navigation styles. Their findings are in agreement with the results of Large et al (2002), indicating that males and females possess different navigation styles while searching information on the Web.…”
Section: Role Of Human Factors In Determining Web User Behavior and Pmentioning
confidence: 99%